Rule-Based Approach For Detecting Advanced Persistent Threat Using Behavioral Features Of Credential Dumping Technique - Ali Mohamed, Nachaat Abdelatif (2022)
The shift from the manual approach of processing data to the digitized method has made organizational data prone to various attacks by cybercriminals. Advanced Persistent Threat (APT) is a recent threat that has ravaged many industries and governments. APT causes enormous damages for data loss, espionage, sabotage, leak, or forceful pay of ransom money to the attackers. Current security measures of addressing APT attack involve detecting the attacks long after it has happened and failed to provide proactive responses. The current security solutions are deployed to detect APT signature and behaviour after APT bypasses the entire protections and accomplishes lateral movement technique, which makes the current solutions ineffective to resolve APT problem.